Evaluasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) di Bagian Rawat Jalan dengan Metode HOT -Fit - Faigayanti, Afriza; Suryani, Lilis; Rawalilah, Hamyatri (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2022)
Accordance with the regulation of the Minister of Health of the Republic of Indonesia No. 82 of 2013 all hospitals shall be held SIMRS. At RSUD Besemah since SIMRS has been implemented, there has never been a SIMRS evaluation. Therefore, the researcher will conduct research by introducing SIMRS in RSUD Besemah using HOT-FIT method. This study aims to see the Net benefit of SIMRS implementation in RSUD Tora Belo Sigi District. This study is Quantitative research with cross sectional design to measure the variable of human, organization, and technolog toward SIMRS net benefit in RSUD Besemah. Since the population is less than 100 then the sample is taken using total sampling technique. Data analysis is done by using SEM PLS and the application name used is SmartPLS version 3.0. The results of this study explain that there are three factors that affect net benefits are: service quality, user satisfaction, environment organization. While the factors that do not have influence on the net benefit SIMRS in Besemah Hospital are: system use, organization structure, system quality, and information quality. The conclusion of The most influential factor in the success of net benefit Hospital Management Information System in Besemah Hospital is service quality, user satisfaction, environment organization